Non-invasive in vivo fluorescence imaging of apoptotic retinal photoreceptors - Francesca Mazzoni (Nature Portfolio, 2019)
Abstract Phosphatidylserine externalization is an early molecular signature for apoptosis. In many retinal degenerative diseases, photoreceptor neurons die by apoptosis. Here, we report utility of the phosphatidylserine-binding conjugate of Bis(zinc(II)-dipicolylamine (Zn-DPA) with Texas-red (PSVue-550) in transiently labeling apoptotic photoreceptors in living pigmented or albino rats and mice with retinal degeneration. Applying PSVue-550 as eyedrop is non-toxic and eliminates need for intraocular injection. PSVue-550 fluorescence specifically and transiently labeling dying retinal photoreceptors is detectable in anesthetized animals using standard retinal or whole small animal imaging systems. Importantly, prior PSVue-550 eyedrop administration and imaging does not affect repeat testing. Altogether, our results establish PSVue-550 imaging as a completely non-invasive method that provides the opportunity to longitudinally monitor retinal photoreceptor cell death in preclinical studies.